Priming medicinal plants with stress signals: a sustainable approach to boosting therapeutic efficacy - Esther Ugo Alum (Journal of Plant Interactions)
Medicinal plants are invaluable to healthcare systems, yet meeting global demand for their therapeutic compounds remains a challenge. Stress priming, involving controlled exposure of plants to abiotic or biotic stressors, has emerged as a sustainable strategy to enhance their resilience and boost the biosynthesis of bioactive secondary metabolites. This commentary explores the molecular mechanisms underlying stress priming, such as the roles of reactive oxygen species (ROS) and phytohormones in initiating defense pathways. Highlighting practical applications, it demonstrates how stress priming enhances the production of alkaloids, flavonoids, and other phytochemicals while reducing reliance on agrochemicals. Despite its potential, optimizing stress protocols and integrating priming into large-scale cultivation pose challenges requiring interdisciplinary research. Stress priming represents a transformative approach to medicinal plant cultivation, offering a pathway to align agricultural practices with global sustainability and healthcare demands.